Comparing the Bacterial Community in the Gastrointestinal Tracts Between Growth-Retarded and Normal Yaks on the Qinghai–Tibetan Plateau - Ma, Jian (Front Microbiol, 2020)
In ruminants, the bacterial community in the gastrointestinal tract (GIT) has an essential role in healthy growth. Examining the bacterial composition in the GIT between growth-retarded and normal yaks could improve our understanding of the role of microorganisms in yaks with growth retardation. In this study, eight male yaks with growth retardation were used as the growth-retarded yak (GRY) group, and another eight male growth normal yaks (GNYs) with the same breed and age were used as the GNY group. We compared the bacterial community in the rumen, duodenum, jejunum, ileum, cecum, and colon between GRY and GNY groups based on the 16S ribosomal RNA gene sequencing. Alpha-diversity revealed that the Shannon index in the duodenum and ileum of the GNY group was higher (P < 0.05) than that of the GRY group. However, the opposite trend was found in the jejunum and cecum. The principal coordinates analysis (PCoA) showed that the bacterial structure in all segments of GIT differed from each other between two groups. In the rumen, the relative abundances of Ruminococcaceae NK4A214 group, Ruminococcaceae UCG-014, and Treponema 2 were higher (P < 0.05) in the GNY group as compared with the GRY group. However, the Christensenellaceae R-7 group exhibited an opposite trend. In the jejunum, compared with the GNY group, the unclassified Chitinophagaceae was enriched significantly (P < 0.05) in the GRY group. However, the unclassified Peptostreptococcaceae, Christensenellaceae R-7 group, and Lachnospiraceae NK3A20 group were enriched (P < 0.05) in the GNY group. In the ileum, the relative abundances of the Rikenellaceae RC9 gut group and Prevotellaceae UCG-004 were higher (P < 0.05) in the GNY group than those in the GRY group. In the cecum, the GNY group showed a higher (P < 0.05) relative abundance of Prevotellaceae UCG-003 as compared with the GRY group. In the colon, the relative abundances of Treponema 2 and unclassified Lachnospiraceae were slightly higher (0.05 < P < 0.10) in the GNY group than those in the GRY group. Overall, these results improve our knowledge about the bacterial composition in the GIT of growth-retarded and normal yaks, and regulating the bacterial community may be an effective solution to promote the compensatory growth of GRYs.